2013
DOI: 10.3109/10717544.2013.866992
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of nanoemulsion: a comparison between phase inversion composition method and high-pressure homogenization method

Abstract: There is lot of confusion in the literatures regarding the method of production of nanoemulsion. According to some authors, only the methods using high energy like high-pressure microfluidizer or high-frequency ultra-sonic devices can produce actual nanoemulsions. In contrast to this concept, one research group reported for the first time the preparation of nanoemulsion by a low-energy method. Later on many authors reported about the low-energy emulsification method. The purpose of this work is to formulate, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
63
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(84 citation statements)
references
References 25 publications
7
63
0
3
Order By: Relevance
“…HPH though possesses the advantage of producing nanoemulsion with slightly smaller droplet size however the droplets in such nanoemulsion are found to have irregular outline; Jafari et al [38] reported this phenomenon due to over-processing. In addition, nanoemulsion with a high PDI [39] as well as most costly operation and tidy maintenance associated with HPH, favor the use of ultrasonication technique. For nanoemulsion formula optimization, sonication time was chosen as independent variable.…”
Section: Preparation Of Drug Loaded Nanoemulsion and Qualitative Optimentioning
confidence: 99%
“…HPH though possesses the advantage of producing nanoemulsion with slightly smaller droplet size however the droplets in such nanoemulsion are found to have irregular outline; Jafari et al [38] reported this phenomenon due to over-processing. In addition, nanoemulsion with a high PDI [39] as well as most costly operation and tidy maintenance associated with HPH, favor the use of ultrasonication technique. For nanoemulsion formula optimization, sonication time was chosen as independent variable.…”
Section: Preparation Of Drug Loaded Nanoemulsion and Qualitative Optimentioning
confidence: 99%
“…Comparing the refractive index (RI) of the NE with water (RI = 1.333), where the closer the NE value to the water value, the more uniform and transparent the NE is. [115,116] In vitro skin permeation Franz diffusion cell apparatus To assess transcutaneous penetration or membrane retention.…”
Section: Characterization Of Transdermal Nementioning
confidence: 99%
“…The necessity for higher amounts of surfactants may be a downside [17]. The whole concept of low energy synthesis has its roots in modification of factors responsible for the hydrophilic-lipophilic balance of the surfactantoil-water mixture [26]. These include environmental factors like temperature, composition and the chemical potential of the components.…”
Section: Low Energy Methodsmentioning
confidence: 99%